2015
DOI: 10.5430/jha.v4n3p39
|View full text |Cite
|
Sign up to set email alerts
|

Complaints concerning communication reported by users of healthcare in a specific region in Sweden

Abstract: Introduction: Effective communication between patients and healthcare staff is important in all healthcare services. Previous studies investigating criticism and complaints concerning treatment reported by patients and relatives in a healthcare context point to the most common complaints were unsatisfactory information, unsatisfactory respect and unsatisfactory empathy, but further investigation is needed. Objective: The aim of this study was to explore complaints reported by patients and relatives in a county… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The reason that this may be particularly important for patients living with HTH wounds can be that they are often treated simultaneously in both primary and secondary healthcare sectors, thus encountering many different nurses and doctors. Based on this, and the findings of a Swedish study who found that most complaints from patients and their relatives are related to lack of communication, inadequate individualistic and holistic healthcare, 40 we encourage healthcare professionals treating this specific patient group to pay attention to patient involvement and communication across healthcare sectors. This is in line with the suggestions by Deufert and colleagues, stating that the Wound‐QoL may be useful for health professionals to expand the focus on patient perspectives in clinical practice 20 …”
Section: Discussionmentioning
confidence: 90%
“…The reason that this may be particularly important for patients living with HTH wounds can be that they are often treated simultaneously in both primary and secondary healthcare sectors, thus encountering many different nurses and doctors. Based on this, and the findings of a Swedish study who found that most complaints from patients and their relatives are related to lack of communication, inadequate individualistic and holistic healthcare, 40 we encourage healthcare professionals treating this specific patient group to pay attention to patient involvement and communication across healthcare sectors. This is in line with the suggestions by Deufert and colleagues, stating that the Wound‐QoL may be useful for health professionals to expand the focus on patient perspectives in clinical practice 20 …”
Section: Discussionmentioning
confidence: 90%
“…78 Body image concerns may not be on the patient's mind when discussing implantation and it is known that an individualistic and holistic involvement and communication with patients from the health care professionals plays a crucial role for patient's satisfaction with the healthcare system and treatment. 79 Therefore, we recommend that health providers ask patients about body image concerns before and after the ICD is implanted, regardless of patients' gender, 11 as such involvement may lead to a decision to submammary implantation and increase patient satisfaction due to reduced body image concerns. 9,10,12 However, this requires an adoption of the method by the clinicians, as this is currently not the standard implantation technique for ICDs, and perhaps not a possible solution for some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Body image concerns should be discussed with the patient before implantation, sharing with them the decision about which ICD is preferable. Good communication between a patient and physician plays a crucial role for the patient's satisfaction with treatment [12], particularly during the decision-making process. It is crucial to avoid a negative impact of the implant on the well-being of patients to reduce depression and anxiety that could increase the risk of ventricular arrhythmias (VAs) and mortality [13], as well as causing general noncompliance with medical treatment [14].…”
Section: S-icd Patients' Acceptancementioning
confidence: 99%